Evaluation of jute leaf as substitute of fish meal in the diet of mrigal (Cirrhinus cirrhosus) fingerlings (International Journal of Agricultural Research, Innovation and Technology, 2020)
The study was conducted to identify jute leaf powder as an alternate to fish meal in diets of juvenile mrigal (Cirrhinus cirrhosus) for 60 days. Tossa jute (Corchorus olitorius) leaf was selected to utilize this unexplored nutritious resource rather leaving under water for potential pollution. Three isonitrogenous test diets were prepared and applied as treatments (T) in triplicates (R). In control (T0) dietary inclusion rate of fish meal was 30%, of which 10% was substituted with jute leaf powder in T10 and in T20 replacement was 20%. Mrigal fingerlings (9.38±0.13 cm and 7.94 ±0.26 g) were stocked in nine plastic half drums (0.26 m2 each) at 10 fish per drum and fed test diets. Although, growth parameters among the treatments were statistically similar, the highest mean length gain, weight gain, SGR and production were 1.51 (±0.18) cm, 2.96 (±0.13) g, 0.53 (±0.03) %/day and 4084.00 (±50.67) kg ha-1, respectively in T10. However, significantly higher (P